ПСИХОЛОГО-ПЕДАГОГІЧНІ АСПЕКТИ ФОРМУВАННЯ ХУДОЖНЬОГО ІНТЕРЕСУ УЧНІВ (Педагогіка вищої та середньої школи, 2009)
The essence of the notion of the artistic interest and its structures is opened in this article by Chebotarenko O.V., Ovcharenko O.S. The new aspects, directions, modern approaches to form the artistic interest of pupils of schools are considered.